2010
DOI: 10.1167/iovs.09-5130
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Relationships in Normal and Glaucomatous Eyes Determined by Time- and Spectral-Domain Optical Coherence Tomography

Abstract: The results showed that, in mild-to-moderate glaucoma, SD-OCT offers an improved structure-function correlation compared with TD-OCT, when applied to the detection of INFERIOR MS and SUPERIOR RNFL defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
1
39
1
1
Order By: Relevance
“…[3][4][5] Fortunately, recent reports have shown that spectral-domain optical coherence tomography (SD-OCT) is useful for measuring ppRNFL thickness, and can therefore be used for detecting early glaucoma including the preperimetric stage. [6][7][8] In contrast, studies have shown that the macular thickness in glaucomatous eyes is significantly less than in normal eyes. [9][10][11] This reduction is attributed mainly to the loss of RGCs and retinal nerve fibers.…”
mentioning
confidence: 97%
“…[3][4][5] Fortunately, recent reports have shown that spectral-domain optical coherence tomography (SD-OCT) is useful for measuring ppRNFL thickness, and can therefore be used for detecting early glaucoma including the preperimetric stage. [6][7][8] In contrast, studies have shown that the macular thickness in glaucomatous eyes is significantly less than in normal eyes. [9][10][11] This reduction is attributed mainly to the loss of RGCs and retinal nerve fibers.…”
mentioning
confidence: 97%
“…The evaluation of circumpapillary RNFL thickness using optical coherence tomography (OCT) has been shown to provide objective and reliable information on glaucomatous optic nerve damage, and has been widely used over several decades. [1][2][3][4][5][6][7][8] The recent advent of spectral-domain OCT (SD-OCT) has enabled a more precise measurement of RNFL thickness and improved its performance compared with earlier time-domain OCT. [9][10][11][12][13] A precise evaluation of circumpapillary RNFL thickness requires correct centering of the OCT scan circle.…”
mentioning
confidence: 99%
“…More recently, however, spectral domain OCT (SD-OCT) devices have become widely available, offering significant advantages over previous TD-OCT devices including higher speed, greater sensitivity, and higher resolution. 15,16 The superior image quality of these SD-OCT devices has allowed a number of anterior segment structures to be clearly identified, including the corneal endothelium and its termination (ie, SL). 17,18 As a result, computation of angle metrics directly based on the actual position of SL are now possible, such as SL-AOD and SL-TISA.…”
mentioning
confidence: 99%